The effect of laboratory critical value reporting on patient management at Siriraj Hospital – Thailand’s largest national tertiary referral center - Preechaya Wongkrajang; Saharat Leelanuwatkul; Sairung Nuanin; Sathima Laiwejpithaya (PLoS ONE, 2025)
Critical laboratory values are life-threatening results that necessitate immediate medical intervention. Reporting these values according to established guidelines is essential for ensuring optimal patient safety and care quality. The aim of this study was to evaluate the laboratory critical value reporting system and the actions taken at Siriraj Hospital – Thailand’s oldest and largest teaching hospital – during January 2018. This study reviewed critical values from hematology, coagulation, and clinical chemistry tests over a one-month period. Patient management actions in response to critical values were classified into five categories: treatment, further investigation, monitoring, treatment combined with investigation, and other. Descriptive statistics were used to analyze the data in Microsoft Excel 2019, calculating the incidence of critical values, notification rates, and management actions. Of the 253,537 tests that were performed, 2,722 critical levels were found, indicating an incidence rate of 1.1%. Hemoglobin and potassium were the most frequently observed critical parameters, accounting for 25.61% and 23.99% of cases, respectively. The rate of notification varied depending on the specific parameter and patient category. For critical glucose and potassium levels, the most common response was close monitoring within 30 minutes, followed by treatment in 80% of cases. Hypermagnesemia, a condition linked to preeclampsia and treated with magnesium sulfate, required particularly careful monitoring. The 1.1% incidence of critical values in this study is high compared to previously published international data; however, this may be explained by the high volume of complex cases referred to our national tertiary referral center. Critical value reporting criteria should be established based on patient conditions and hospital management practices to reduce unnecessary alerts, optimize laboratory workload, and ensure high-quality patient care.